C5-selective trifluoromethylation of 8-amino quinolines via photoredox catalysis - Tian, Chao; Yang, Li-Ming; Tian, Hai-Tao; An, Guang-Hui; Li, Guang-Ming (Journal of fluorine chemistry, 2019)
[Display omitted] •A transition-metal free, site-selective, visible-light mediated trifluoromethylation protocol was achieved.•The reaction was carried in environmental benign solvent enabled by organo photocatalyst.•This protocol allowed rapid access to a series of aminoquinoline amides, including 8-aminoquinoline tosylamide. A new protocol for C5-selective CH trifluoromethylation of 8-aminoquinolines via photoredox catalysis was developed. It allows rapid access to various C5-trifluoromethyl 8-amino quinoline derivatives in MeCN/H2O enabled by Eosin Y as photocatalysts.